Festival Film sebagai Praktik Budaya: Studi Pengalaman Audiens Muda di Jogja-NETPAC Asian Film Festival 2024 - Ardila Ayu Setyo Putri; Fajar Dwi Putra (Yayasan Literasi Sains Indonesia, 2025)
Film festivals are not merely screening spaces but cultural arenas that enable young audiences to create meaning through collective experiences. This study aims to examine the experiences of young audiences at the 19th Jogja-NETPAC Asian Film Festival (JAFF) as a cultural practice, using a cultural studies approach and Michel de Certeau’s theory of everyday tactics. A qualitative descriptive method was employed through in-depth interviews with three informants, all film and television students, who participated as both audiences and volunteers. The findings indicate that JAFF is perceived as a space for learning, self-expression, and building social networks. Young audiences employ various tactics, such as joining as volunteers, engaging in film communities, and utilizing social media as an extension of the festival experience. Q&A and discussion sessions emerge as vital cultural participation spaces, fostering critical engagement and collaborative initiatives beyond the festival. The study concludes that JAFF functions as a cultural laboratory where young audiences negotiate their identities and construct meaning through active participation.